2019
DOI: 10.1186/s12894-019-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of histamine receptors in the bladder wall tissues of patients with bladder pain syndrome/interstitial cystitis – significance in the responsiveness to antihistamine treatment and disease symptoms

Abstract: BackgroundActivation of mast cells plays an important role in the pathogenesis of bladder pain syndrome/interstitial cystitis (BPS/IC). Histamine, a mast cell-derived mediators, induced inflammation and hypersensitivity of the bladder. The present study investigated the expressions of histamine receptors in the bladder wall tissues of patients with BPS/IC, and its association with the effectiveness of antihistamine therapy and disease symptoms.MethodsBladder tissues were collected from 69 BPS/IC patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Meanwhile, mast cells can be visible in the uroepithelial, lamina propria, and smooth muscle layers of the bladder wall. The activation of mast cells causes the release of histamine, the binding of which to the receptors on the bladder wall causes inflammation and bladder sensitization (20). Moreover, histamine can also increase the afferent nerve's bladder sensitivity via H1 receptors, leading to overactive bladder contractions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, mast cells can be visible in the uroepithelial, lamina propria, and smooth muscle layers of the bladder wall. The activation of mast cells causes the release of histamine, the binding of which to the receptors on the bladder wall causes inflammation and bladder sensitization (20). Moreover, histamine can also increase the afferent nerve's bladder sensitivity via H1 receptors, leading to overactive bladder contractions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Release of histamine from MCs is considered to be related to inflammation and hypersensitivity of the bladder. Shan et al studied the expression of histamine receptors within the bladder of women with BPS/IC [ 30 ] and identified increased expression of all four histamine receptors in the BPS/IC group compared with the control group. Although we report no treatment outcomes for this study, the authors would explore the association of bladder mastocytosis with a possible diagnosis of MC activation syndrome and would consider treatment with a trial of diet restrictions to avoid MC-liberating foods in combination with MC-stabilising or suppression therapy [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, data regarding mast cells is mixed with a recent study showing higher levels of mast cells in non-Hunner's lesion patients [71]. Interestingly, a recent study has shown that histamine receptor expression is upregulated in patients with BPS/IC, but this did not predict response to antihistamine treatment [72]. The question of whether an elevated mast cell count represents a distinct phenotype of BPS independent of the presence of Hunner's lesions remains to be determined.…”
Section: Histopathological Featuresmentioning
confidence: 97%
“…A small retrospective study compared the outcomes of amitriptyline treatment in patients with BPS/IC stratified according to ESSIC criteria and found no difference in efficacy between ESSIC type 1 and ESSIC type 3 patients [28]. Similarly, another retrospective study comparing antihistamine responders to non-responders found no correlation between the expression levels of histamine receptors and treatment outcome, although patients were not stratified by cystoscopic features [72]. Outcomes from intravesical hyaluronic acid instillations cannot be predicted by the presence or absence of Hunner's lesions, and data for superior efficacy for intravesical dimethylsulfoxide (DMSO) in Hunner's lesion patients compared with non-Hunner's lesion patients comes from a small, retrospective study [78,79].…”
Section: Response To Treatmentmentioning
confidence: 99%